IS POPULISM A THREAT FOR THE EXISTENCE OF REPRESENTATIVE DEMOCRACY OR ITS CORRECTIVE MECHANISM? - Stašienė, Jogilė (Politologija, 2016)
While the success of populist political parties has been increasing in Western Europe, politicians are becoming more concerned with the populist threat for representative democracy. However, scholars of populism have different perspectives on what influence populism might have on representative democracy. One group of researchers perceive populism as fundamentally hostile to the principles of the representative democracy. Other scientists understand populism as corrective for democracy or at least a part of it. The article attempts to answer the question why some populism theorists treat populism as incompatible with representative democracy, and others interpret it as a corrective for democracy. To answer the question, it has been analysed how two opposing groups of populism scholars define populism, representative democracy and how they conceptualise the relationship between them. The first group of scholars – Paul Taggart, Margaret Canovan and Benjami Arditi – understand populism as an attempt to deal with the imperfections of democracy. Populism mobilises indifferent people to participate in the decision making process, attempts to reduce the gap between representatives and the represented, and suggests decreasing an excessive regulation of democracy. Populism is corrective for democracy as long as it corrects the existing institutions or replaces them by new ones. However, if populists seek to replace the institutions with the direct governance by the leader or by the people, it might lead to rulers with unconditional power. Populists simplify the political process and perceive the people as a homogeneous unit. As a result, pluralism, political parties, and the rules of the political process are rejected. Nadia Urbinati and Gianfranco Pasquino belong to the second group of the scholars of populism. They define populism as a set of ideas to seek the power and to implement direct governance of the people without institutional constraints. Democracy, on the other hand, is understood from the institutionalist point of view: as a collection of procedures and regulations. Populism poses a threat to representative democracy because of the ideology of unity of the people which can be implemented through abolishing procedures and regulations. Political parties, which communicate and represent the interests of the people, are not necessary, because society does not have inner divisions to begin with. A leader is to replace different institutions, as well as discussions, deliberations, and compromises, and to implement the will of the people. While populism is being defined in similar terms by both group of scholars, it can be concluded that the disagreement lies in the differing conceptions of representative democracy. According to the institutionalist perspective of democracy (N. Urbinati and G. Pasquino), populism is a constant threat to representative democracy because it attempts to eliminate procedures and institutions – the essence of democracy. P. Taggart, B. Arditi, and M. Canovan, on the other hand, present the concept of two-strand democracy as composed of an institutional side and of a side of popular will. Populism brings out the side of popular will and criticises the institutional side of democracy, therefore providing an opportunity to revive the pragmatic pole of democracy through the popular inclusion in the decision making process.